Hadith #5219 - Sunan Abi Dawud - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Iyas bin Dghfl إياس بن دغفل; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل (Sunan Abi Dawud)
the prophet (ﷺ) said; Good tidings to you, ‘A’ishah, for Allah Most High has revealed your innocence. He then recited to her the Quranic verses. Her parents said: Kiss the head of the Messenger of Allah (ﷺ). I said : Praise be to Allah, most High, not to you.
Grade: Sahih